HISTOLOGICAL STRUCTURE OF BALI DUCKS SKIN IN GROWER PHASE - Dionysius Immanuel; Ni Luh Eka Setiasih; Ni Nyoman Werdi Susari; I Ketut Berata; Luh Gde Sri Surya Heryani; Sri Kayati Widyastuti (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
The skin is the largest and outermost organ that can be directly observed. The skin plays a crucial role for bali ducks as a protective barrier against the environment, maintaining body temperature, retaining body fluids, and neurosensory functions. This study aims to determine the structure of the bali duck skin (Anas sp.) during the grower phase. This study used ten bali ducks aged 3 months. The histological structure was observed using a binocular light microscope. The histological structure was analyzed descriptively and qualitatively. The structure of bali duck skin consists of three layers: epidermis, dermis, and hypodermis. The epidermis has three layers: stratum corneum, stratum intermedium, and stratum basale. The dermis has two layers: stratum compactum and stratum laxum. The tissues found in the bali duck skin include feather follicles, blood vessels, Herbst corpuscles, connective tissue, and musculus erector pili. Based on the research conducted, no differences in the histological structure of the skin were found across the three regions. Further research is needed on the skin structure of Bali ducks at different phases and sexes to obtain more comprehensive data, and specific histological studies are required to identify the skin histology of Bali ducks in greater detail.